The Influence Of Service Quality On Customer Satisfaction In Surabaya Tourist Destinations During The Covid-19 Pandemic - Yuniawati Ekaningrum; Fredianaika Istanti; Evada El Ummah Khoiro (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
The long-term goal of the study is to find out if the tourism industry can survive the Covid-19 pandemic while still prioritizing the quality of services in accordance with health protocols. The type of research is descriptive analysis with a quantitative approach. The population in the study was the visitors to three tourist destinations in Surabaya, namely the Submarine Museum, House of Sampoerna and Surabaya Zoo. The number of samples used was 100 respondents using accidental sampling techniques, namely respondents who were accidentally encountered at the time the questionnaire was distributed. The collected data was analyzed using multiple regression analysis with SPSS 23.0 software. The results showed that the variables of service quality (realibility, responsiveness, assurance, emphaty, and tangibles) have a positive and significant influence on tourist satisfaction